Influence of visual impairment level on the regulatory mechanism used in the long jump - Panoutsakopoulos, V.; Theodorou, A. S.; Kotzamanidou, M. C.; Skordilis, E.; Plainis, S.; Kollias, I. A. (New Studies in Athletics, 2015)
The purpose of the study was to investigate how visually impaired long jumpers regulate their strides during the approach and adjust the technique of the final strides to prepare for the take-off. The attempts of 35 visually impaired class Fll, FI 2 and F13 long jumpers at the 2009 International Blind Sports Association European Championships in Rhodes, Greece, were analysed. No significant differences (p>.05) were observed among the jumpers of different classes concerning velocity, stride frequency and stride length in the last steps of the approach. Analysis revealed that visually impaired athletes are able to perceive time-to-contact to the take-off area and act in a regulatory manner. Additionally, angle of takeoff increased as the visual impairment increased. Finally, a more rapid knee flexion of the take-off leg was observed for F13 jumpers fp<.05), resulting in a larger maximum knee flexion (p<05) during the taken off. It is possible that factors such as the size and surface properties of the take-off area used in F12 and F13 competitions contribute to these differences.